Evaluation of a hybrid antimicrobial restriction process at a large academic medical center - Jesse D. Smith; Linh H. Nguyen; Tamara Krekel; Jerrica Waggoner; David J. Ritchie; Michael J. Durkin; Kevin Hsueh; Elizabeth A. Neuner (Cambridge University Press, 2021)
We conducted a retrospective review of a hybrid antimicrobial restriction process demonstrating adherence to appropriate use criteria in 72% of provisional-only orders, in 100% of provisional orders followed by ID orders, and in 97% of ID-initiated orders. Therapy interruptions occurred in 24% of provisional orders followed by ID orders.